Expression of Fluorescent Cyclotides using Protein Trans‐Splicing for Easy Monitoring of Cyclotide–Protein Interactions1. Issue 11 (15th January 2013) - Jagadish, Krishnappa; Borra, Radhika; Lacey, Vanessa; Majumder, Subhabrata; Shekhtman, Alexander; Wang, Lei; Camarero, Julio A.
<x xml:space="preserve">Abstract</x> Going in circles: Expression of cyclotides containing non‐natural amino acids (see scheme; gray sphere) inside live bacterial cells was accomplished using a highly efficient split intein in combination with nonsense codon suppressor tRNA technology. Cyclotides containing p‐azidophenylalanine can be expressed in live bacterial cells and easily labeled using copper‐free click chemistry to monitor the cyclotide–protein interactions.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>